PENGEMBANGAN MEDIA PEMBELAJARAN BERBANTUKAN KOMPUTER (COMPUTER ASSISTED INSTRUCTION/CIA) UNTUK PEMBELAJARAN KIMIA SMA - Holiwarni, Betty (SOROT, 2014)
The objective of this research is to develop instructionalmedia assisted by computer which is valid, practical, and effective toinstructional high school chemistry at Atomic Structure and ChemicalBonding subject. The method of this research is developmentresearch. The research is held for two years and consist of 4 stages,define, design, develop, and disseminate. The research in the firstyear is as far as the development stage. Research data were collectedthrough assessment form filled by the validator. The result showedthat instructional media assisted by computer which is developed forhigh school chemistry lesson at Atomic Structure and ChemicalBonding subject meeting the valid criteria in terms of content andconstruction.